Customer satisfaction with online shopping: Shopee / Syukrina Alini Binti Mat Ali ... [et al.] - Mat Ali, Syukrina Alini; Mohd Ali, Ainunnazlee; Saiful Bahry, Norliza; Mohd Salleh, Mohammad Zaim; Mat, Azmi (Universiti Teknologi Mara Selangor, 2023)
This study seeks to provide an overview of the elements that influence shoppers' desire when using the Shopee platform. Thus, it focuses on users of Shopee who frequently conduct online shopping and how satisfied they are with the platform or service they use. Shopee is a well-known and rapidly expanding online marketplace for shopping. Many people have benefited from this online shopping platform by using it as an affordable means of buying a variety of commodities or products. The study will concentrate on the seller's response, the efficiency of the delivery, the quality of the goods and the price of the products in relation to the customers' happiness with online shopping. Given this trend, it is critical to comprehend and analyze the variables influencing customer satisfaction in online buying.